(untitled) (Perner’s Contacts, 2014)
Article is aimed to evaluate the applicability of the SBM, which is focused on area of rail transport. The aim of this paper is to analyze the method of legal point of view and identify appropriate methods that could be used in specific specified procedure. Compares similar methods for risk assessment of common safety methods and subsequently identify the advantages and disadvantages of its practical using.